Ancient genomes from northern China suggest links between subsistence changes and human migration - Chao Ning (Nature Portfolio, 2020)
Northern China contains some of the world’s earliest farming societies. Here, authors use 55 ancient genomes to trace the genetic history of human migrations across northern China for the last 7500 years, and document genetic changes mirroring shifts in subsistence strategy.